2018
DOI: 10.1016/j.nbd.2018.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Pretangle pathology within cholinergic nucleus basalis neurons coincides with neurotrophic and neurotransmitter receptor gene dysregulation during the progression of Alzheimer's disease

Abstract: Cholinergic basal forebrain neurons of the nucleus basalis of Meynert (nbM) regulate attentional and memory function and are exquisitely prone to tau pathology and neurofibrillary tangle (NFT) formation during the progression of Alzheimer’s disease (AD). nbM neurons require the neurotrophin nerve growth factor (NGF), its cognate receptor TrkA, and the pan-neurotrophin receptor p75NTR for their maintenance and survival. Additionally, nbM neuronal activity and cholinergic tone are regulated by the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 132 publications
(199 reference statements)
4
24
2
Order By: Relevance
“…2A). Co-staining of the dendritic marker MAP2 with Cav-1 showed decreased MAP2 expression in the hippocampal CA1 subfield and cortex in PSAPP-SynRFP, similar to that observed in postmortem human brains of patients diagnosed with CTE, tauopathy, and AD [17,18]. In contrast, PSAPP-SynCav1 mice displayed increased hippocampal (Fig.…”
Section: Syncav1 Preserves Mlr-localization Of Cav-1 and Trkb In Hippsupporting
confidence: 77%
See 1 more Smart Citation
“…2A). Co-staining of the dendritic marker MAP2 with Cav-1 showed decreased MAP2 expression in the hippocampal CA1 subfield and cortex in PSAPP-SynRFP, similar to that observed in postmortem human brains of patients diagnosed with CTE, tauopathy, and AD [17,18]. In contrast, PSAPP-SynCav1 mice displayed increased hippocampal (Fig.…”
Section: Syncav1 Preserves Mlr-localization Of Cav-1 and Trkb In Hippsupporting
confidence: 77%
“…One such gene therapy candidate is caveolin-1 (Cav-1), a MLR scaffolding protein that organizes NTRs (Trk) and neurotransmitter receptor signaling complexes in MLRs [12][13][14]. Both pre-clinical and clinical findings revealed that Cav-1 and Cav-1 associated signaling complexes (NTRs and neurotransmitter receptors) were decreased in degenerating neurons in AD, chronic traumatic encephalopathy (CTE), and amyotrophic lateral sclerosis (ALS) [15][16][17][18]. In contrast, we previously showed that neuron-targeted Cav-1 over-expression (i.e., synapsin-promoted Cav-1 or SynCav1) augmented agonist-mediated synaptic signaling (e.g., NTRs, neurotransmitter receptors) and dendritic arborization in vitro [12], preserved MLR-localized TrkB and extended life span in ALS mice [19], suggesting that alterations in Cav-1 expression affects pro-survival signaling and neuroprotection in neurodegenerative conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Expression of another FTDP-17 mutant tau, A152T, in C. elegans neurons led to abnormal localization of synaptic vesicles that may be due to minor disruptions in aFAT and rFAT independent of any tau aggregation or changes to microtubule binding [14,73]. These studies do not identify a specific signaling pathway, but the conclusions may be similar to observed impairment of aFAT and rFAT by tau filaments phosphorylated at S422 [93], a disease-specific phosphorylation event that occurs early in pre-tangles and robustly labels neuropil threads in areas of the brain involved in memory and cognition [32,94]. Such observations suggest that certain modifications in tau may expose PAD and other domain(s) that in turn activate alternative signaling pathways.…”
Section: Tau-based Effects On Fast Axonal Transport Tau and Regulatormentioning
confidence: 90%
“…Another consideration is that this investigation examined PreC CatDimmunopositive neurons irrespective of NFT status. Since we did not differentiate NFT-positive or negative neurons, as done in prior studies (Tiernan et al, 2016(Tiernan et al, , 2018, we were unable to attribute the effect of tau pathology on specific expression profiles during the progression of dementia. This neuronal distinction will be investigated upon access Volunteer subjects may introduce bias by decreasing pathology but this, in part, is mitigated by the high follow-up and autopsy rates of the RROS cohort (Bennett et al, 2005).…”
Section: Discussionmentioning
confidence: 93%